PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN CANVA DENGAN BERBANTUAN AUGMENTED REALITY PADA MATERI GOTONG ROYONG DI SDN 14 INDRALAYA UTARA - Yuliastuti, Septi; Nabilah Mansur; Siti Dewi Maharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media based on Canva integrated with Augmented Reality (AR) technology on mutual cooperation material for fourth grade students of SDN 14 Indralaya Utara. The development model used is Research and Development (R&D) with the ADDIE approach, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. These stages are designed to ensure that the media produced is in accordance with student needs and the curriculum, and is effective in delivering character material. The validation process was carried out by media experts, material experts, and two education practitioners to assess the feasibility of the content, visual appearance, language, and suitability of the media to learning outcomes. The validation results showed a validity level of 93.1% which is included in the Very Valid category. Meanwhile, the practicality test through one-to-one and small group trials with fourth grade students obtained an average percentage of 97.4% (Very Practical category). These findings prove that the interactive learning media based on Canva and AR that were developed are not only feasible and valid, but also practical for use by students and teachers. This media is able to help students understand the value of mutual cooperation in a more contextual, visual, and interactive way, so that it can be an alternative innovation in character learning in elementary schools.